Pemecahan Sandi Kriptografi dengan Menggabungkan Metode Hill Cipher dan Metode Caesar Chipher - Wardani, Indria Eka (CAUCHY, 2013)
Message is a privacy statement which is made by a person and addressed to another person with the consent of people who have made the message. But with the development of modern technology resulted in a high level of privacy for their safety message. Especially lately act haeker (security breaker) are increasingly rampant and alarming message makers. To address this, the authors will examine and discuss the cryptographic cipher to convey a secret message privacy. Message in the form of a password using cryptography in this paper Combining of Hill Cipher Method and Caesar Cipher Methods.In the operation process of encryption and decryption passwords cryptography, the steps using the Caesar CipherMethods, whereas in steps using keys by using Hill Cipher method. In the making and the first decoding the message makers and recipients know how the operation technique. Thus the expected delivery of message privacy secured.